Strengths employed by resilient nurse managers in dealing with workplace stressors in public hospitals - Thokgamo Boitshwarelo; Magdalene P. Koen; Mahlasela A. Rakhudu (Elsevier, 2020)
Background: Nurse managers work in complex health care environments that expose them to challenging workplace conditions. As nurse managers face significant workplace stressors, some will succumb to the pressure and stress contemplating to leave for other opportunities or even leave the profession. However, the resilient nurse managers seem to adapt, recover and have the strengths required to manage workplace stressors. Objective: To explore and describe the strengths that resilient nurse managers employ when dealing with work related stress.Setting and sampling: A purposive sampling method was used with resilient nurse managers working in the general wards of the public hospitals in Botswana.Participants: A total of forty-two (42) resilient nurse managers who measured moderate to high resilience participated in the study. Methods: A qualitative exploratory design was used in the study. Data was collected through written narratives guided by a semi-structured data collection tool. Thematic analysis was used to identify strengths that resilient nurse managers utilized while dealing with workplace stressors. Results: The main themes that emerged from the study were: upholding personal values, employing life skills, applying appropriate leadership skills and access to social support. Conclusions: The study revealed that the identified resilient nurse managers utilized their strengths and other resilient characteristics in dealing with workplace stressors. These strengths are used as buffers in dealing with workplace stressors, enabling them to overcome difficulties and provide quality nursing services.